Model Project Based Learning dalam Pembelajaran Biologi: Suatu Penelitian Tindakan Kelas di SMA Negeri 2 Langowan - Kirei Hana Megumi Moniung; Ferny M. Tumbel; Wiesye M. S. Nangoy (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
The low activity of students in biology learning is the main challenge in efforts to improve the quality of science learning in secondary schools. This study aims to analyze the effectiveness of the application of the Project Based Learning learning model in increasing student activity and learning outcomes in respiratory system materials at SMA Negeri 2 Langowan. This research is a Class Action Research that is carried out in two cycles, each of which includes stages of planning, action, observation, and reflection. The subjects of the study were 13 students in grade XI. The instruments used include student activity observation sheets and the final test of the cycle based on description questions. The results showed that in the first cycle, only 38.46% of students achieved learning completeness with an average score of 60. However, after improving the strategy in cycle II through active mentoring, learning motivation, and strengthening group work, completeness increased to 92.30% with an average score of 84.69. These findings indicate that the Project Based Learning learning model is able to build student activeness through contextual, collaborative, and hands-on experience-based learning. The increase in activeness is reflected not only in test results, but also in students' active participation in discussions, group presentations, and project completion. The implications of this study show that Project Based Learning is feasible to be implemented as an innovative learning strategy to improve the quality of student interaction and engagement in biology learning on an ongoing basis.